Sentiment and social capital in aid project: Chagas disease control in Honduras. Issue 1 (1st January 2017) - Ueda, Naoko
Abstract: This article aims to analyze the relationship between aid donor interventions and sentiment in the context of social capital, and to consider how sentiment changes in community members influence sustained changes in their behavior. The author analyzed the effects of the Chagas Disease Control Project implemented from 2003 to 2011 in Honduras by conducting a qualitative study of community members and project participants. Three common themes were identified: happiness, sense of achievement, and pride. This project created an "exchange of responses" between health administrations and communities by stimulating the intrinsic motivation of people concerned and generating positive sentiment among them, thereby creating social capital that supported the self-sustained vector control. The interventions of the project were: (1) activities that ensured achievement visibility; (2) having Japanese staff accompany Honduran staff in the field; and (3) promoting development of awareness, knowledge, and action on multiple levels in the people involved.